Analysis of anther dehydration: a process required for anther dehiscence and pollen release - Dennis, Ruth (2018)
In flowering plants, the opening of the anther to release pollen is carefully timed to maximise reproductive potential. Manipulation of this process is an important tool for plant breeding and the production of hybrid crops. Dehydration of the anther epidermis, combined with the presence of secondary thickening within the endothecium layer, is required to create biomechanical changes that enable anther dehiscence. Both passive and active processes contribute to the targeted removal of water from the anther walls, however the genetic factors controlling water movement are not known. Furthermore, the presence of stomata on anthers may enhance water loss via evaporation. In plants, active movement of water can be achieved by regulation of water channels and by changes to the osmotic potential of organs; this was explored in the context of changes in the anther driving anther dehiscence and pollen release. qRT-PCR analysis was used to identify aquaporin and sucrose transporter genes that are upregulated during anther dehiscence in Arabidopsis thaliana. For genes of interest, the phenotypes of available mutants were characterised. Combinations of single, double and triple mutants showed changes in fertility and variations in floral organ lengths. Analysis of GUS reporter lines showed that the promoter activity of different aquaporins is confined to specific parts of the flower. The results suggest that certain aquaporins isoforms enhance hydraulic conductivity in different parts of the flower, which could contribute to water transport required for petal and filament extension. The importance of evaporation during anther dehydration was also investigated. The phenotypes of Arabidopsis mutant lines with varying stomatal densities were characterised, and changes in fertility were investigated under different environmental conditions. High relative humidity delayed anther dehiscence and affected pollen viability, resulting in reduced fertility. Plants that have no anther stomata were most severely affected. These results suggest that water loss via evaporation is important for anther opening in Arabidopsis, and that the presence of stomata on anthers facilitates this process.